Obstructed Umbilical Hernia with Cecal Perforation and Omphalitis: A Unique Case in an Infant - Amar Shah; Ria Sharma; Aryan Momin; Anirudh Shah (Journal of Indian Association of Pediatric Surgeons)
Umbilical hernia is very commonly encountered in infants. Obstruction in an umbilical hernia, though rare, has been reported in literature. We report a rare case of a 2-month-old boy who had an obstructed cecum in the umbilical hernia with localized perforation and omphalitis.